2021
DOI: 10.18178/ijiet.2021.11.12.1578
|View full text |Cite
|
Sign up to set email alerts
|

Categories for Barriers to Digital Transformation in Higher Education: An Analysis Based on Literature

Abstract: For higher education institutions that encourage digital transformation, understanding the barriers are necessary for the digital transformation accomplishment. The purpose of this paper is to present a review of the literature on barriers to digital transformation in higher education. To get a wide overview in identifying the barriers to the implementation of digital transformation, a structured literature review was used to select the relevant studies published. Nine categories were identified based on the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 26 publications
0
36
0
1
Order By: Relevance
“…A final issue is the relationship of the present study to previous attempts to organize the existing literature [4,12,13]. These studies focused on understanding and systematizing the literature based on a few dozen articles.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A final issue is the relationship of the present study to previous attempts to organize the existing literature [4,12,13]. These studies focused on understanding and systematizing the literature based on a few dozen articles.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding past authors' attempts to order the existing literature, several previous publications were identified. However, these publications had different objectives than those of the present study: Aditya, Ferdina, and Kusumawardani [12] focused only on systematizing the barriers to digital transformation in HEIs. Alenezi [13] focused on reviewing the digital maturity models applicable to HEIs.…”
Section: Digital Transformation In Heismentioning
confidence: 95%
“…Many studies are concentrated on DT barriers in higher education. Aditya et al (2021a), in their state-of-the-art study of the digital transformation barriers in higher education based on a structured literature review, have identified 22 barriers that formed nine categories shown in Figure 1.…”
Section: Barriersmentioning
confidence: 99%
“…Figure1. The fishbone diagram of barriers to digital transformation in higher education(Aditya et al, 2021a) …”
mentioning
confidence: 99%
See 1 more Smart Citation